Calcium signalling of human pluripotent stem cell-derived cardiomyocytes - Li, Sen (Blackwell Science Inc, 2013)
Loss of cardiomyocytes (CMs), which lack the innate ability to regenerate, due to ageing or pathophysiological conditions (e.g. myocardial infarction or MI) is generally considered irreversible, and can lead to conditions from cardiac arrhythmias to heart failure. Human (h) pluripotent stem cells (PSCs), including embryonic stem cells (ESC) and induced pluripotent stem cells (iPSCs), can self-renew while maintaining their pluripotency to differentiate into all cell types, including CMs. Therefore, hPSCs provide a potential unlimited ex vivo source of human CMs for disease modelling, drug discovery, cardiotoxicity screening and cell-based heart therapies. As a fundamental property of working CMs, Ca(2+) signalling and its role in excitation–contraction coupling are well described. However, the biology of these processes in hPSC-CMs is just becoming understood. Here we review what is known about the immature Ca(2+)-handling properties of hPSC-CMs, at the levels of global transients and sparks, and the underlying molecular basis in relation to the development of various in vitro approaches to drive their maturation.